1987
DOI: 10.1128/mcb.7.5.1764
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of the Saccharomyces cerevisiae CRY1 gene: a highly conserved ribosomal protein gene.

Abstract: The Saccharomyces cerevisiae CRY] gene encodes ribosomal protein rp59, a component of the 40S ribosomal subunit. Mutations in CRY] can confer resistance to the alkaloid cryptopleurine, an inhibitor of the elongation step of translation. The nucleotide sequence of the cloned CRY] gene was determined. The predicted amino acid sequence shows that CRY] encodes a 14,561-dalton polypeptide that has 88% amino acid sequence homology to the hamster or human S14 ribosomal protein responsible for emetine resistance and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 73 publications
1
54
0
Order By: Relevance
“…Levy, in prep.). Although the arrangement of the tripartite consensus promoter motifs common to yeast ribosomal protein genes (Rotenberg and Woolford 1986;Larkin et al 1987) differs between the two RPL16 genes (see Fig. 7; Rotenberg and Woolford 1986), we have not been able to correlate these specific arrangements with levels of transcription of each gene.…”
Section: Discussionmentioning
confidence: 78%
“…Levy, in prep.). Although the arrangement of the tripartite consensus promoter motifs common to yeast ribosomal protein genes (Rotenberg and Woolford 1986;Larkin et al 1987) differs between the two RPL16 genes (see Fig. 7; Rotenberg and Woolford 1986), we have not been able to correlate these specific arrangements with levels of transcription of each gene.…”
Section: Discussionmentioning
confidence: 78%
“…The 40S subunit ribosomal protein S 14, encoded in yeast by the CRY1 gene, has been highly conserved throughout eukaryotic evolution (Chen et al 1986;Larkin et al 1987). Therefore, this yeast gene seemed likely to be an effective hybridization probe for the isolation of a maize ribosomal protein eDNA.…”
Section: Isolation Of Z Mays Cdna Clones Homologous To the Yeast S14mentioning
confidence: 99%
“…When the amino acid alignment shown in Figure 2B is used and excluding gaps are introduced to maintain sequence alignment, 77% of the amino acids (105 of 137) are identical between MCH1 and the yeast S14 ribosomal protein (Larkin et al 1987), and 88% (129 of 147) of the amino acids are identical between MGH1 and the CHO cell S14 ribosomal protein (Rhoads and Roufa 1985). The predicted MCH2 gene product is slightly less conserved relative to the CHO cell and yeast proteins (76 and 87% amino acid identity, respectively).…”
Section: Isolation Of Z Mays Cdna Clones Homologous To the Yeast S14mentioning
confidence: 99%
See 1 more Smart Citation
“…The small subunit protein RPS14, the yeast homolog of the bacterial S11 protein, directly binds helix 23 of 18S rRNA (Fewell and Woolford Jr., 1999;Mayolo and Woolford Jr., 2003). Recently, it was reported that RPS14 is an essential protein necessary for the maturation of the 40S ribosomal subunit (Larkin et al, 1987;Moritz et al, 1990;Paulovich et al, 1993;Ford et al, 1999;Jakovljevic et al, 2004) and the processing of 18S pre-rRNA (Ferreira-Cerca et al, 2005;Ebert et al, 2008). And in the 40S subunit, RPS14 helps to form the mRNA exit channel along with its interacting protein RPS5 (Yusupov et al, 2001).…”
Section: Introductionmentioning
confidence: 99%